Improved quantum efficiency in an engineered light harvesting/photosystem II super-complex for high current density biophotoanodes. Issue 29 (27th May 2020) - Hartmann, Volker; Harris, Dvir; Bobrowski, Tim; Ruff, Adrian; Frank, Anna; Günther Pomorski, Thomas; Rögner, Matthias; Schuhmann, Wolfgang; Adir, Noam; Nowaczyk, Marc M.
Abstract : Integration of a 10 MDa light-harvesting photosystem II super-complex into macro-puorous indium tin oxide biophotoanodes for improved energy conversion. Abstract : Photosystem II (PSII) is the only enzyme that catalyzes light-induced water oxidation, the basis for its application as a biophotoanode in various bio-photovoltaics and photo-bioelectrochemical cells. However, the absorption spectrum of PSII limits the quantum efficiency in the range of visible light, due to a gap in the green absorption region of chlorophylls (500–600 nm). To overcome this limitation, we have stabilized the interaction between PSII and Phycobilisomes (PBSs) – the cyanobacterial light harvesting complex, in vitro . The PBS of three different cyanobacteria ( Acaryochloris marina, Am, Mastigocladus laminosus, ML, and Synechocystis sp. PCC 6803, Syn ) are analyzed for their ability to transfer energy to Thermosynechococcus elongatus ( Te ) PSII by fluorescence spill-over and photo-current action spectra. Integration of the PBS–PSII super-complexes within an Os-complex-modified hydrogel on macro-porous indium tin oxide electrodes (MP-ITO) resulted in notably improved, wavelength dependent, incident photon-to-electron conversion efficiencies (IPCE). IPCE values in the green gap were doubled from 3% to 6% compared to PSII electrodes without PBS and a maximum IPCE up to 10.9% at 670 nm was achieved.